A Rare Histological Entity- Oral Fibrolipoma - Debta, Priyanka; Debta, F.M; Bhuyan, Ruchi; Siddhartha, Saswati; Goyal, Prashant Kumar; Mohanty, Sandeep (International Journal of Medical and Health Sciences Research, 2016)
Among lipoma of oral cavity, fibrolipoma is one of the rare histopathological variant. Intraoral lipomas are rare lesions which may be discovered during routine dental examinations since they present as slow growing, painless and asymptomatic masses. For definite diagnosis histopathological examination plays a significant role in providing successful treatment and preventing any malignant transformation. Prognosis is generally good as recurrence is very rare. Here we present a case of oral fibrolipoma of buccal mucosa.